Residential exposure to noise, green space, and children’s language acquisition - Xing Yu; Ingrid Jarvis; Matilda van den Bosch; Martin Guhn; Hind Sbihi; Hugh Davies (Environment International)
Background: Noise pollution has been linked to impaired development in a variety of language-related skills in laboratory settings. While studies have focused on school environments, residential noise exposure’s impact remains underexplored. Methods: We used multilevel regression models to examine the association between noise exposure measured using deterministic noise modelling and language development in kindergarten-aged children in Vancouver, Canada, between April 1, 2000 and December 31, 2005, measured through a questionnaire completed by kindergarten teachers (the Early Development Instrument). The models were adjusted for median income level and English as a Secondary Language (ESL) status, as well as random effects on teachers, and we explored the potential interaction effects of greenness, measured using satellite imagery. Results: The study included 33,153 children for which there were data on noise exposure and indicators of language development. The mean noise level was 63.5 dB(A), and the mean percentage of greenness within a 250-meter radius buffer zone was 31.8 %. We found that an increase in residential exposure to noise independently increased the odds of not meeting developmental expectations in basic literacy (OR: 1.18, 95 % CI: 1.12–1.25), advanced literacy (OR: 1.11, 95 % CI: 1.07–1.16), and communication and general knowledge (OR: 1.10, 95 % CI: 1.06–1.14). Greenness was found to have interaction effects with basic and advanced literacy skills in noisy environment. Conclusion: This study found residential exposure to noise was associated with poorer language development outcomes, with interaction effects of greenness observed in literacy skills. Future studies should also examine the long-term effects of residential exposure to noise on language development.